The effect of conventional surgery and piezoelectric surgery bone harvesting techniques on the donor site morbidity of the mandibular ramus and symphysis - Altıparmak, Nur; Soydan, Sıdıka Sinem; Uçkan, Sina (Churchill Livingstone, 2015)
The aim of this study was to evaluate the morbidity following bone harvesting at two different intraoral donor sites, mandibular symphysis and ramus, and to determine the effects of piezoelectric. and conventional surgical graft harvesting techniques on donor site morbidity. Intraoral block bone grafts were harvested from the symphysis (n = 44) and ramus (n = 31). The two donor site groups were divided into two subgroups according to the surgical graft harvesting method used (conventional or piezoelectric surgery). Intraoperative and postoperative pain was assessed using a visual analogue scale (VAS). Donor site morbidity and the harvesting techniques were compared statistically. Of 290 teeth evaluated in the symphysis group, four needed root canal treatment after surgery. The incidence of transient paresthesia in the mucosa was significantly higher in the symphysis group than in the ramus group (P = 0.004). In the symphysis group, the incidence of temporary skin and mucosa paresthesia was lower in the piezoelectric surgery subgroup than in the conventional surgery subgroup (P = 0.006 and P = 0.001, respectively). No permanent anaesthesia of any region of the skin was reported in either donor site group. VAS scores did not differ between the ramus and symphysis harvesting groups, or between the piezoelectric and conventional surgery subgroups. When the. symphysis was chosen as the donor site, minor sensory disturbances of the mucosa and teeth were recorded. The use of piezoelectric surgery during intraoral harvesting of bone blocks, especially from the symphysis, can reduce these complications.
WOS: 000360419000012
PubMed ID: 25979191
Keywords: Bone Block Grafts; Bone Augmentation; Piezoelectric Surgery; Autologous Bone Grafts; Morbidity